Numerical Study of Hall Thruster Plume and Sputtering Erosion - Li Yan; Ping-Yang Wang; Yang-Hua Ou; Xiao-Lu Kang (Journal of Applied Mathematics)
Potential sputtering erosion caused by the interactions between spacecraft and plasma plume of Hall thrusters is a concern for electric propulsion. In this study, calculation model of Hall thruster’s plume and sputtering erosion is presented. The model is based on three dimensional hybrid particle-in-cell and direct simulation Monte Carlo method (PIC/DSMC method) which is integrated with plume-wall sputtering yield model. For low-energy heavy-ion sputtering in Hall thruster plume, the Matsunami formula for the normal incidence sputtering yield and the Yamamura angular dependence of sputtering yield are used. The validation of the simulation model is realized through comparing plume results with the measured data. Then, SPT-70’s sputtering erosion on satellite surfaces is assessed and effect of mass flow rate on sputtering erosion is analyzed.